NMDA receptors in the lateral hypothalamus have an inhibitory influence on the tachycardiac response to acute restraint stress in rats - Deolindo, Milena V.; Reis, Daniel G.; Crestani, Carlos Cesar [UNESP]; Tavares, Rodrigo F.; Resstel, Leonardo B.M.; Corrêa, Fernando M.A. (Wiley, 2013)
The aim of the present study was to investigate the role of the lateral hypothalamus (LH) and its local glutamatergic neurotransmission in the cardiovascular adjustments observed when rats are submitted to acute restraint stress. Bilateral microinjection of the nonspecific synaptic inhibitor CoCl2 (0.1 nmol in 100 nL) into the LH enhanced the heart rate (HR) increase evoked by restraint stress without affecting the blood pressure increase. Local microinjection of the selective N-methyl-d-aspartate (NMDA) glutamate receptor antagonist LY235959 (2 nmol in 100 nL) into the LH caused effects that were similar to those of CoCl2. No changes were observed in the restraint-related cardiovascular response after a local microinjection of the selective non-NMDA glutamatergic receptor antagonist NBQX (2 nmol in 100 nL) into the LH. Intravenous administration of the muscarinic cholinergic receptor antagonist homatropine methyl bromide (0.2 mg/kg), a quaternary ammonium drug that does not cross the blood-brain barrier, abolished the changes in cardiovascular responses to restraint stress following LH treatment with LY235959. In summary, our findings show that the LH plays an inhibitory role on the HR increase evoked by restraint stress. Present results also indicate that local NMDA glutamate receptors, through facilitation of cardiac parasympathetic activity, mediate the LH inhibitory influence on the cardiac response to acute restraint stress. The bilateral microinjection of the CoCl2 or LY235959 into the LH enhanced the HR increase evoked by restraint stress without affecting the blood pressure increase. Intravenous administration of the homatropine methyl bromide abolished the changes in cardiovascular responses to restraint stress following LH treatment with LY235959. These results suggest that such LH influence is mediated by local NMDA glutamate receptors and involves parasympathetic nervous activation. © 2013 Federation of European Neuroscience Societies and John Wiley & Sons Ltd.
Keywords: Autonomic activity; Cardiovascular response; Hypothalamus; NMDA receptors; Stress; 6 nitro 7 sulfamoylbenzo[f]quinoxaline 2,3 dione; homatropine methyl bromide; n methyl dextro aspartic acid receptor; autonomic nervous system; blood brain barrier; cardiovascular response; controlled study; facilitation; heart rate; histology; immobilization stress; lateral hypothalamus; lung artery pressure; male; mean arterial pressure; microinjection; neurotransmission; nonhuman; parasympathetic function; priority journal; rat; stimulus response; tachycardia